Reactive nonsexually related acute genital ulcers. (13th October 2017) - Ueda, Yoshitaka; Kamiya, Koji; Ohtsuki, Mamitaro
Abstract : The case of a 19‐year‐old Japanese woman with reactive nonsexually related acute genital ulcers.